Enumeration of Microbes and Microbial Activities in Coastal Saline Soils of Eastern India - and Archana Mai Naik, K. Laxminarayana (Journal of the Indian Society of Soil Science, 2016)
An investigation was carried out to study the effect of salinity on microbes and enzyme activities of the salt-affected soils in five districts of Odisha, India adjacent to Bay of Bengal in relation to physicochemical properties. The soils are strongly acidic to slightly alkaline, and having a salinity of 2.28 to 8.11 dS m-1, low in organic C and available N, and medium in available P and K. The microbial populations were relatively lower in these saline soils, and bacterial population dominant over that of fungi and actinomycetes. Soil biological activity in terms of dehydrogenase and fluorescein diacetate activities in the saline soils varied from 0.89 - 2.11 µg TPF h-1 g-1 soil and 0.91 to 2.31 µg g-1 h-1, respectively. Acid phosphatase activity was relatively higher (27.8 - 64.2 µg p-nitrophenol g-1 soil h-1) than alkaline phosphatase activity (17.8 - 55.9 µg p-nitrophenol g-1 soil h-1) and influencing the P transformations. Among the various soil groups, Vertisols had higher status of available nutrients and enzyme activities followed by Inceptisols, Alfisols and Entisols. Salinity had negative relationship with all microbial variables and chemical properties of the soil, indicating that the increase in soluble salt content affects severely the biochemical transformations that regulate inherent soil fertility. Since majority of soil biochemical transformations are dependent on presence of microbes and microbial activities, the present investigation emphasized the intervention of suitable strategies for maintenance of soil quality in order to realize higher crop productivity in the coastal regions.